Trends In Islamic Thought Today (Wacana Syari'at Islam Sebagai Hukum Positif Di Indonesia) - Hamzah Tualeka Zn (Al Hikmah, 2017)
Lord Meghnad Desai brings three forms of Islamism , Islamism moral , Islamism National and Global Islamism . Islamism moral , is that the Muslim-majority country should act according to the teachings of Islam . National Islamism , is that if there is a Muslim majority , the government should follow the Qur'an as a guide and Sharia law , and so on . Global Islamism is that Muslims must understand the history of underdevelopment (after glory for seven centuries) and fought reclaiming power.